Measurement invariance of the Childhood Autism Rating Scale (CARS) across six countries. Issue 12 (4th August 2021) - Stevanovic, Dejan; Costanzo, Floriana; Fucà, Elisa; Valeri, Giovanni; Vicari, Stefano; Robins, Diana L.; Samms‐Vaughan, Maureen; Ozek Erkuran, Handan; Yaylaci, Ferhat; Deshpande, Smita N.; Deshmukh, Vaishali; Arora, Narendra K.; et al.
Abstract: The Childhood Autism Rating Scale (CARS) is a simple and inexpensive tool for Autism spectrum disorder (ASD) assessments, with evidenced psychometric data from different countries. However, it is still unclear whether ASD symptoms are measured the same way across different societies and world regions with this tool, since data on its cross‐cultural validity are lacking. This study evaluated the cross‐cultural measurement invariance of the CARS among children with ASD from six countries, for whom data were aggregated from previous studies in India ( n = 101), Jamaica ( n = 139), Mexico ( n = 72), Spain ( n = 99), Turkey ( n = 150), and the United States of America ( n = 186). We analyzed the approximate measurement invariance based on Bayesian structural equation modeling. The model did not fit the data and its measurement invariance did not hold, with all items found non‐invariant across the countries. Items related to social communication and interaction (i.e., relating to people, imitation, emotional response, and verbal and nonverbal communication) displayed lower levels of cross‐country non‐invariance compared to items about stereotyped behaviors/sensory sensitivity (i.e., body and object use, adaptation to change, or taste, smell, and touch response). This study found that the CARS may not provide cross‐culturally valid ASD assessments. Thus, cross‐cultural comparisons with the CARS should consider first which items operate differently across samples of interest, since its cross‐cultural measurement non‐invariance could be a source of cross‐cultural variability in ASD presentations. Additional studies are needed before drawing valid recommendations in relation to the cultural sensitivity of particular items. Lay Summary: The Childhood Autism Rating Scale (CARS) is a widely used and inexpensive tool for autism assessments across the globe. We tested its cross‐cultural validity among children with autism from India, Jamaica, Mexico, Spain, Turkey, and the United States of America. All CARS items operated differently across these countries, which indicates that they may not provide cross‐culturally valid assessments. Comparing CARS data across regional and linguistically diverse samples requires first determining which items operate differently across the samples.